The Leadership Role of the Principal in Managing Facilities and Infrastructure at Mutiara Hidayah PAUD - Anwar Abu Bakar; Ujang Cepi Barlian; Fenti Sanda; Yuliana Ambarwati (al-Afkar, Journal For Islamic Studies, 2023)
The aims of this study were (1) to determine the extent of the principal's leadership role in the management of facilities and infrastructure in Mutiara Hidayah PAUD. Planning the leadership role of the school principal in managing facilities and infrastructure, to find out the supervision of the leadership role of the school principal in managing facilities and infrastructure. (2) the approach used in this research is a qualitative approach, which is a research procedure that produces descriptive data in the form of speech or writing and behavior that can be observed from the subject itself (Furhan: 1992, 21). (3) conclusions and research results from research at Mutiara Hidayah PAUD found that the role of the principal in managing infrastructure is very important in supporting the success of teaching activities. The school principal prioritizes the educational needs of students, the comfort of students and the needs of their teachers through facilities and infrastructure. The fulfillment of these needs and behaviors will lead to high trust from parents and society. By positioning the principal as a multifunctional person, he will know and feel all the ups and downs of his subordinates. He always has discussions about all the problems and planning of education in his school.